Youth Unemployment and Vocational Training - Biavaschi, Costanza; Eichhorst, Werner; Giulietti, Corrado; Kendzia, Michael J.; Muravyev, Alexander; Pieters, Janneke; Rodríguez-Planas, Nuría; Schmidl, Ricarda; Zimmermann, Klaus F. (World Bank, Washington, DC, 2013)
This report focuses on the determinants of the labor market situation of young people in devel-oped countries and the developing world, with a special emphasis on the role of vocational training and education policies. We highlight the role of demographic factors, economic growth and labor market institutions in explaining young people‘s transition into work. We then assess differences in the setup and functioning of the vocational education and training policies in major world regions, as an important driver of differential labor market situation of youth. Based on our analysis we argue in favor of vocational education and training systems combining work experience and general education and give some policy recommendations regarding the implementation of education and training systems adapted to a country‘s economic and institutional context.